2011
DOI: 10.1007/s12350-011-9458-9
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and predictive accuracy of quantitatively defined transient ischemic dilation of the left ventricle on otherwise normal SPECT myocardial perfusion imaging studies

Abstract: In the setting of otherwise normal MPI, elevated TIDr has a low prevalence and poor predictive accuracy and should not be considered summarily as a marker of high risk CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…When incorporated into stress/rest SPECT screening protocols, TID could provide additional information for severe CAD (4, 8). Although the exact significance of quantitatively elevated TID in patients with normal or minimal perfusion abnormality remains unclear and some studies showed that TID had a low prevalence and poor predictive value in the otherwise normal MPI (1112), the presence of TID in patients with abnormal myocardial perfusion abnormality, such as those in our study, has previously been shown to be associated with extensive and severe coronary artery disease (1, 4, 7, 13, 14), as well as a strong independent predictor of future cardiac events (15, 16). However, different scanning protocols may have different normal limits for TID ratios (8, 9), and these have not been well established.…”
Section: Introductionmentioning
confidence: 99%
“…When incorporated into stress/rest SPECT screening protocols, TID could provide additional information for severe CAD (4, 8). Although the exact significance of quantitatively elevated TID in patients with normal or minimal perfusion abnormality remains unclear and some studies showed that TID had a low prevalence and poor predictive value in the otherwise normal MPI (1112), the presence of TID in patients with abnormal myocardial perfusion abnormality, such as those in our study, has previously been shown to be associated with extensive and severe coronary artery disease (1, 4, 7, 13, 14), as well as a strong independent predictor of future cardiac events (15, 16). However, different scanning protocols may have different normal limits for TID ratios (8, 9), and these have not been well established.…”
Section: Introductionmentioning
confidence: 99%
“…The findings regarding TID are supported by those of a previous study by Abidov et al 35 which reported that patients with a high TID and otherwise normal SPECT-MPI or minimal perfusion defects more commonly had severe or extensive CAD incorporating 3VD or >90% stenosis in the proximal LAD as defined by ICA. Some recent papers, however, have reported that TID is not a predictor of extent, severity or high risk of CAD among patients with normal MPI 3638 . Regarding abnormal EF/EF response abnormalities of EF response have been shown to be related to the severity of the coronary artery stenoses as defined by ICA 39 .…”
Section: Discussionmentioning
confidence: 90%
“…Valdiviezo et al studied a cohort of normal perfusion imaging and found no association of TID and multi-vessel disease (15). Mandour et al, found that TID had predictability in patients with perfusion abnormalities but not in the setting of normal perfusion (16). …”
Section: Tid and Its Significance On Coronary Angiographymentioning
confidence: 99%